2008
DOI: 10.1002/chem.200800532
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cooperativity through Design: Pendant CoIIISalen Polymer Brush Catalysts for the Hydrolytic Kinetic Resolution of Epichlorohydrin (Salen=N,N′‐Bis(salicylidene)ethylenediamine Dianion)

Abstract: The Co(III)--salen-catalyzed (salen=N,N'-bis(salicylidene)ethylenediamine dianion) hydrolytic kinetic resolution (HKR) of racemic epoxides has emerged as a highly attractive and efficient method of synthesizing chiral C(3) building blocks for intermediates in larger, more complex molecules. HKR reaction rates have displayed a second order dependency on the concentration of active sites, and thus researchers have proposed a bimetallic transition state for the HKR mechanism. Here we report the utilization of pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 59 publications
2
71
1
Order By: Relevance
“…In the proposed bimetallic transition state of the Co-salencatalyzed hydrolytic kinetic resolution (HKR) mechanism, this flexibility greatly affected the catalyst performance. [14,21] In the monometallic mechanism of the Ru-salen cyclopropanation reaction, this flexibility could be less important. However, the linker does impact the steric hindrance of the polymer backbone near the catalytically active site, which can be important for polymer-supported catalysts in general.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the proposed bimetallic transition state of the Co-salencatalyzed hydrolytic kinetic resolution (HKR) mechanism, this flexibility greatly affected the catalyst performance. [14,21] In the monometallic mechanism of the Ru-salen cyclopropanation reaction, this flexibility could be less important. However, the linker does impact the steric hindrance of the polymer backbone near the catalytically active site, which can be important for polymer-supported catalysts in general.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of polymer resin-supported Ru(II)-salen bis-pyridine catalysts [a: 5 was synthesized via thiol coupling of mercaptopropyltrimethoxysilane (MPTMS) with styryl-salen 2a at 46% isolated yield. [14,25] Compound 5 was immobilized on 60 mesoporous SBA-15 silica by condensation with surface hydroxy groups forming material 6. Unreacted silanol groups were capped with hexamethyldisilazane (HMDS) to form material 7 prior to the metallation procedure with n-butyllithium and ruthenium dimer.…”
Section: Sba-15-supported Ru-salen Catalyst (8): Synthesis and Characmentioning
confidence: 99%
See 2 more Smart Citations
“…It is of interest in this context that binuclear analogues of many catalysts that rely on bimetallic interactions show enhanced activity when compared to monomeric species, examples include certain Ru and Os diporphyrin H 2 evolving catalysts with cofacial orientation (24,25). In one noteworthy case, Jones and coworkers (26,27) showed that a "bisalen" analogue of Jacobsen's Co-(salen) catalyst for hydrolytic kinetic resolution of racemic epoxides (a reaction that also shows a second-order dependence on catalyst concentration) maintained activity when linked to a solid support, whereas the immobilized monomer was essentially inactive (26)(27)(28). Because one of our goals is construction of a catalytic cobaloxime-modified electrode for water reduction, we have investigated the reactivity of a covalently-linked dicobalt complex.…”
mentioning
confidence: 99%